Academic Listening Practices and Synodality: Reflections from a Study of World Youth Days - Charles Mercier (Journal of Moral Theology, 2024)
In order to analyze the possible contribution of academic listening practices to the synodal process, this article offers a reflexive analysis of two social science studies of World Youth Days. The first investigation is a historical work carried out between 2017 and 2020 on John Paul II’s World Youth Days, based on archives and testimonies collected in seven different countries. The second is a sociological and anthropological study carried out in July-August 2023 on the occasion of the WYD in Lisbon: as part of a delegation of pilgrims, the author experienced the pilgrimage in Portugal among the young people and their chaplains, while carrying out research work. At the crossroads of epistemological reflection and life review, the paper presents the opportunities and risks of such empirical research from the viewpoints of the researcher, respondents, and Catholic institution. While highlighting misunderstandings that can arise, the article emphasizes the mutual enrichment academic listening practices in a church setting can bring. If the researcher and researched agree to let go of their rigidities, their companionship can purify both faith and science by desacralizing what should not be sacred.